KOMUNIKASI TRANSEDENTAL MELALUI JUZ AL QURAN - Anggraini, Siti (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2013)
Tracidental communication through Quran by Juzs are actually is very meaningfull, powerfull and it is very interestingthat we should know more about it. Although there are many people todays are forget about what is themeaningful core about transedental communication, mostly they will prefer to convince something for their selfby to what they see in the first place.Moreover, this good information is in your hands now, hopefully it could reflect into your mind soul. In the meanttime we will find out for what the secrets are about Quran behind your usefull life today.